2015
DOI: 10.1007/s10910-015-0480-z
|View full text |Cite
|
Sign up to set email alerts
|

A forgotten topological index

Abstract: In 1972, within a study of the structure-dependency of total π -electron energy (E), it was shown that E depends on the sum of squares of the vertex degrees of the molecular graph (later named first Zagreb index), and thus provides a measure of the branching of the carbon-atom skeleton. In the same paper, also the sum of cubes of degrees of vertices of the molecular graph was shown to influence E, but this topological index was never again investigated and was left to oblivion. We now establish a few basic pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
368
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 689 publications
(370 citation statements)
references
References 8 publications
1
368
0
1
Order By: Relevance
“…In 2015, Fortula and Gutman [12,13] introduced the forgotten topological index and for α = 2 in (1.1) turns it as a very special case formula, defined by…”
Section: D(u)d(v)mentioning
confidence: 99%
See 1 more Smart Citation
“…In 2015, Fortula and Gutman [12,13] introduced the forgotten topological index and for α = 2 in (1.1) turns it as a very special case formula, defined by…”
Section: D(u)d(v)mentioning
confidence: 99%
“…Note that forgotten topological index [12] has only few lower bounds. At first, we give an upper bound for M 3 1 (G) which leads to the upper bound for χ 2 (G).…”
Section: Upper Bounds For χ 2 (G)mentioning
confidence: 99%
“…The forgotten topological index F (G) [8] and the inverse degree sum r(G) [16] of a graph G are two degree based topological indices. These are defined as…”
Section: Introductionmentioning
confidence: 99%
“…Furtula and Gutman in 2015 [12] studied this index again and named as "forgotten topological index" or "F-index". In that paper they showed that the predictive ability of this index is almost similar to that of first Zagreb index and for the entropy and acetic factor, both of them yield correlation coefficients greater than 0.95.…”
Section: Introductionmentioning
confidence: 99%